Newly released fragrant hybrid tea variety of rose – Pusa Mahak - Raju, D V S; Singh, Kanwar Pal; Prasad, K V; Namita, Namita; Singh, Markandey; Sindhu, S S; Dhama, A S (Indian Horticulture, 2020)
The plants are tall and vigorous with a height of 100- 120 cm. The Flowers are dark pink in colour and have outstanding fragrance. The flowering starts in 40-45 days after pruning. Flowers are large and semi-double having 22-23 petals. It is a recurrent/repeat flowering and floriferous variety and each plant produces on an average 55-60 flowering shoots in a season.